Natural Search User Interfaces for Complex Biomedical Search: An Eye Tracking Study. Issue 4 (8th November 2017) - Liu, Ying-Hsang; Thomas, Paul; Bacic, Marijana; Gedeon, Tom; Li, Xindi
Abstract: Controlled vocabularies such as Medical Subject Headings (MeSH) have been extensively used to organise information resources in the biomedical domain. However, the usefulness of these terms for information access has not been rigorously evaluated in interactive search environments. The objective of this study was to gain an understanding of domain experts' interactions with novel search interfaces within the context of biomedical information search, with a goal of better interface design of information retrieval systems. An eye tracking study of biomedical domain experts' interactions with novel search interfaces was conducted, considering user's individual differences and gaze behaviour. The findings suggest that types of search interfaces have significant effects on gaze behaviour in terms of fixation-based measures of areas of interest, i.e. visual attention to the elements of title, author, abstract and MeSH terms in document surrogates. Significant interaction effects between cognitive style and user interaction with search interfaces were found, specifically the amount of attention to MeSH terms by analytic and wholistic searchers. These findings contribute to our understanding of the relationship between cognitive styles and gaze patterns in information search. Based on these findings, the implications of individual differences and gaze behaviour for search interface design are discussed.